Teachers’ Strategies: Can It Prevent Bullying to Early Childhoods in Preschool Education? - Rahmawati, Risa; Hodijah, Dede Siti; Ihsanda, Nu'man; Susiyani, Neni; Sugiarti, Sri; Tya, Sandi (Journal Corner of Education, Linguistics, and Literature, 2024)
Bullying is an action of verbal and non-verbal violences done repeatedly by a person to another. This study aims to determine the forms of bullying carried out by early childhood and teachers’ strategies applied to overcome bullying behavior in preschool education. The method used in this study is a qualitative under a descriptive approach. The findings of the present study show that bullying carried out by early childhoods is in the forms of aggressive and negative actions such as kicking, pinching, hitting, taunting, and pushing friends. In addition, the strategies used by the teachers to prevent bullying behavior to the early childhood are carried out through several steps: (1) the teachers conducted anti-bullying during the teaching and learning process through storytelling method using hand puppet as media related to bullying material, (2) the teachers invited the early childhoods to sing the song to know anti-bullying, (3) the teachers communicated to the parents about the dangers of bullying, (4) the teachers invited the parents to understand well their early childhood’s character, (5) the teachers invited the parents to participate in parenting program, (6) the teachers advised and supervised the early childhoods when they are at school, (7) the teachers provided strict policy against bullying behavior. In conclusion, bullying behavior can be prevented earlier through instilling character education and implement seven strategies such as mentioned above.